PENERAPAN BEADING EMBROIDERY DENGAN KOMBINASI CABOCHON TECHNIQUE SEBAGAI HIASAN PADA EVENING GOWN - Sumardani, Pipin Tresna P., Sona (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2021)
Evening gown is one type of party dress that is divided according to the time of use, namely late afternoon or late evening. Evening gowns usually have more prominent characteristics than other types of party dress. Both of the model and decoration/garniture. The application of beads as an evening gown decoration is one way to impress a luxurious impression of evening party dress. Beads or in English called "beads" comes from the Middle English bede which means "prayer" (object of Worship). Because at first the beads were associated with occult things in previous religious ceremonies. Beads are usually made of stone, bone, wood, shell, glass, metal, and so on. The technique of stringing beads is known as beading embroidery. Beading embroidery is usually done by stringing beads on fabric using the help of a needle and thread. One of the techniques in making beading embroidery is the Cabochon technique. The term of Cabochon comes from French which means head, this term is often used for gemstones that have been polished so that it has a smooth round shape. In its development, the cabochon is decorated with small beads strung around a large gemstone which is likened to the head or center of this ornament..The study aims to 1) To apply the knowledge obtained from the course milineris accessories and Houte Couture as the basis in making milineris accessoires and garniture on the evening gown. 2) To introduce beading embroidery especially the cabochon technique as one of the alternative for garniture or ornament on the evening gown,and 3) To improve the studentâ€™s creativities in making garniture on the evening gown through making beadingÂ  embroidery with cabochon technique. This kind of study is experimental study. The method used is the PBL (Project Base Learning) method. Namely learning methods that use projects / activities as a medium by conducting exploration, assessment, interpretation, synthesis, and information to produce various forms of learning outcomes.